# NCERT Solutions for Class 12 Maths

Find 100% accurate solutions for NCERT Class XII Maths. All questions have been explained and solved step-by-step, to help you understand thoroughly. Free Download option available!

1.

2.

3.

4.

5.

6.

7.

8.

9.

10.

11.

12.

13.

14.

15.

16.

17.

18.

19.

20.

21.

22.

23.

24.

25.

26.

27.

28.

29.

30.

31.

32.

33.

34.

35.

36.

37.

38.

39.

40.

41.

42.

43.

44.

45.

46.

47.

48.

49.

50.

51.

52.

53.

54.

55.

56.

57.

58.

59.

60.

61.

62.

63.

64.

65.

66.

67.

68.

69.

70.

71.

72.

73.

74.

75.

76.

77.

78.

79.

80.

81.

82.

83.

84.

85.

86.

87.

88.

89.

90.

91.

92.

93.

94.

95.

96.

97.

98.

99.

100.

101.

102.

103.

104.

Comparing coefficients x, of 2A = 6 ⇒ A = 3

Comparing constants, -9A + B = 7

On solving, we get A = 3, B = 34

Putting the values of A and B in eq. (ii),

6x + 7 = 3(2x – 9) + 34

Putting this value of 6x + 7 in eq. (i),

105.

Comparing coefficients of x, –2A = 1 ⇒ A =

Comparing constants, 4A + B = 2

On solving, we get A = , B = 4

Putting the values of A and B in eq. (ii),

106.

Comparing coefficients of x, 2A = 1 ⇒ A =

Comparing constants, 2A + B = 2

On solving, we get A = , B = 1

Putting the values of A and B in eq. (ii),

107.

Comparing coefficients of x, 2A = 1 ⇒ A =

Comparing constants, -2A + B = 3

On solving, we get ⇒ A = , B = 4

Putting the values of A and B in eq.(ii), x + 3 = (2x – 2) + 4

Putting this value of x + 3 in eq.(i),

108.

109.

110.

111.

Comparing coefficients of x on both sides A + B = 1 …….(ii)

Comparing constants 2A + B = 0 …….(iii)

Solving eq. (ii) and (iii), we get A = -1 and B = 2

Putting these values of A and B in eq. (i),

112.

113.

Comparing coefficients of x2 : A + B + C = 0 ….(ii)

Comparing coefficients of x : -5A – 4B – 3C = 3

⇒ 5A + 4B + 3C = -3    …(iii)

Comparing constants: 6A + 3B + 2C = –1 ……….(iv)

On solving eq. (i), (ii) and (iii), we get A = 1, B = –5, C = 4

Putting the values of A, B and C in eq. (i),

114.

Comparing coefficients of x2 : A + B + C = 0    ….(ii)

Comparing coefficients of x : -5A – 4B – 3C = 1

⇒ 5A + 4B + 3C = -1       ….(iii)

Comparing constants: 6A + 3B + 2C = 0 ……….(iv)

On solving eq. (i), (ii) and (iii), we get

Putting the values of A, B and C in eq. (i),

115.

Comparing coefficients of x on both sides A + B = 2 ……….(ii)

Comparing constants 2A + B = 0 …….(iii)

Solving eq. (ii) and (iii), we get A = -2 and B = 4

Putting these values of A and B in eq. (i),

116.

Comparing coefficients of on both sides

Comparing constants A = 1 ……….(iv)

Solving eq. (ii) and (iii), we get

Putting these values of A and B in eq. (ii),

117.

Comparing coefficients of A + C = 0 ……….(ii)

Comparing coefficients of , –A + B = 1 ……….(iii)

Comparing constant terms, –B + C = 0 ……….(iv)

Solving eq. (ii), (iii) and (iv), we get

Putting the values of A, B and C in eq.(i),

118.

Comparing coefficients of x2 : A + C = 0 ……….(ii)

Comparing coefficients of x : A + B – 2C= 1 ……….(iii)

Comparing constants: –2A + 2B + C = 0 ……….(iv)

On solving eq. (i), (ii) and (iii), we get

Putting the values of A, B and C in eq. (i),

119.

Comparing coefficients of x2 : A + C = 0 ……….(ii)

Comparing coefficients of x : B – 2C= 3 ……….(iii)

Comparing constants: –2A + B + C = 5 ……….(iv)

On solving eq. (i), (ii) and (iii), we get

Putting the values of A, B and C in eq. (i),

120.

Comparing coefficients of x2 : 2A + 2B + C = 0 ……….(ii)

Comparing coefficients of x : 5A + B = 2 ……….(iii)

Comparing constants: 3A – 3B – C = –3 ……….(iv)

On solving eq. (i), (ii) and (iii), we get

Putting the values of A, B and C in eq. (i),

121.

Comparing coefficients of x2 : A + +B + C = 0 ……….(ii)

Comparing coefficients of x : –B + 3C = 5 ……….(iii)

Comparing constants: –4A – 2B + 2C = 0 ……….(iv)

On solving eq. (i), (ii) and (iii), we get

Putting the values of A, B and C in eq. (i),

122.

123.

Comparing the coefficients of x2 A – B = 0 ……….(ii)

Comparing the coefficients of x B – C = 0 ……….(iii)

Comparing constants A + C = 2 ……….(iv)

On solving eq. (ii), (iii) and (iv), we get A = 1, B = 1, C = 1

Putting these values of A, B and C in eq. (i),

124.

125.

Comparing the coefficients of y A + B = 0 ………(ii)

Comparing constants A – B = 1 ……….(iii)

On solving the eq. (ii) and (iii), we get

Putting the values of A, B and in eq. (i),

126.

127.

128.

Comparing coefficients of y A + B = –4 ……….(v)

Comparing constants 4A + 3B = –10 ……….(vi)

On solving eq. (v) and (vi), we get A = 2, B = –6

Putting the values of A, B and y in eq. (iii),

129.

130.

131.

132.

Comparing coefficients of x A + B = 1 ……….(ii)

Comparing constants –2A – B = 0 ……….(iii)

On solving eq. (ii) and (iii), we get A = –1, B = 2

Putting these values of A and B in eq. (i),

Therefore, option (B) is correct.

133.

134.

135.

136.

137.

138.

139.

140.

141.

142.

143.

144.

145.

146.

147.

148.

149.

150.

151.

152.

153.

154.

155.

156.

157.

158.

159.

160.

161.

162.

163.

164.

165.

166.

167.

168.

169.

170.

171.

172.

173.

174.

175.

176.

177.

178.

179.

180.

181.

182.

183.

184.

185.

186.

187.

188.

189.

190.

191.

192.

193.

194.

195.

196.

197.

To change the limits of integration from x to t

when x = 0, t = x2 + 1 = 0 + 1 = 1

when x = 1, t = x2 + 1 = 1 + 1 = 2

∴ From eq. (i),

198.

199.

200.

201.

202.

203.

204.

205.

206.

207.

208.

209.

210.

211.

212.

213.

214.

215.

216.

217.

218.

219.

220.

221.

222.

223.

224.

225.

226.

227.

228.

Comparing the coefficients of x2 –A + B – C = 0 ……….(ii)

Comparing the coefficients of x B + C = 0 ……….(iii)

Comparing constants A = 1 ……….(iv)

On solving eq. (ii), (iii) and (iv), we get

Putting these values in eq. (i),

229.

230.

231.

232.

233.

Comparing coefficients of x2 A + B = 0 ……….(iii)

Comparing coefficients of x B + C = 5 ……….(iv)

Comparing constants 9A + C = 0 ……….(v)

On solving eq. (iii), (iv) and (v), we get

Putting these values of A, B and C in eq. (ii),

234.

235.

236.

237.

238.

239.

240.

241.

242.

243.

244.

245.

246.

247.

248.

249.

Comparing coefficients of x2 A + C = 1 ……….(iii)

Comparing coefficients of x 3A + B + 2C = 1 ……….(iv)

Comparing constants 2A + 2B + C = 1 ……….(v)

On solving eq. (iii), (iv) and (v), we get A = –2, B = 1, C = 3

Putting these values of A, B and C in eq. (ii),

250.

251.

252.

253.

254.

255.

Putting sin x – cos x = t

⇒ (cos x + sin x) dx = dt

Again (sin x – cos x)2 = t2

⇒ sin2 x + cos2 x – 2 sin x cos x = t2

⇒ sin 2x = 1 – t2

256.

257.

Putting sin x – cos x = t

⇒ (cos x + sin x) dx = dt

Again (sin x – cos x)2 = t2

⇒ sin2 x + cos2 x – 2 sin x cos x = t2

⇒ sin 2x = 1 – t2

Limits of integration when x = 0, t = 0 – 1 = -1 and

258.

259.

260.

261. Taking RHS

Comparing coefficients of x A + C + 0 ……….(iii)

Comparing coefficients of x A + B = 0 ……….(iv)

Comparing constants B = 1

On solving eq. (iii), (iv) and (v), we get A = -1, B = 1, C = 1

Putting these values of A, B and C in eq. (ii),

262.

263.

264.

265.

266.

267.

268.

269.

270.

271.

MySchoolPage connects you with exceptional, certified maths tutors who help you stay focused, understand concepts better and score well in exams!